2003
DOI: 10.1038/sj.bjc.6600986
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid induces antiproliferative and apoptotic effects in human pancreatic cancer cells in vitro

Abstract: Bisphosphonates (BPs) are an emerging class of drugs mostly used in the palliative care of cancer patients. We investigated the in vitro activity of the most potent antiresorptive BP, zoledronic acid (ZOL), on the growth and survival of three human pancreatic cancer (PC) cell lines (BxPC-3, CFPAC-1 and PANC-1). Pancreatic cancer frequently has a dysregulated p21 ras pathway and therefore appears to be a suitable target for BPs that interfere with the prenylation of small GTP-binding proteins such as p21 ras . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
117
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 40 publications
4
117
0
1
Order By: Relevance
“…After ZOL exposure however, the distribution of MSH2 protein changed markedly and adopted a peri-nuclear and cytoplasmic distribution, figure 7. Similarly, for PARP-1, its fulllength form p116 exhibited an 81% decrease in the ZOL-treated sample and more than 400% increase in the PAM-treated sample, indicating a higher degree of (27), prostate cancer (28) and multiple myeloma (33), pancreas (24). We found evidence of significant antiproliferative effects in a range 10-100 mol, consistent with previous studies.…”
Section: Mechanism Of Apoptotic Deathsupporting
confidence: 90%
See 2 more Smart Citations
“…After ZOL exposure however, the distribution of MSH2 protein changed markedly and adopted a peri-nuclear and cytoplasmic distribution, figure 7. Similarly, for PARP-1, its fulllength form p116 exhibited an 81% decrease in the ZOL-treated sample and more than 400% increase in the PAM-treated sample, indicating a higher degree of (27), prostate cancer (28) and multiple myeloma (33), pancreas (24). We found evidence of significant antiproliferative effects in a range 10-100 mol, consistent with previous studies.…”
Section: Mechanism Of Apoptotic Deathsupporting
confidence: 90%
“…In pancreatic cancer lines, commonly associated with p21ras dysregulation, the effects of BP was to interfere with growth and survival pathways downstream of p21 ras. ZOL treatment resulted in apoptotic death and caspase 9 (but not caspase 3) activation (24).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…48 However, in most of these studies, long incubation periods and high concentrations of zoledronic acid were used, conditions not achievable in vivo. Following i.v.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Both molecules are involved in the post-translational isoprenylation of key regulator proteins including small GTPbinding proteins such as Ras, Rho, and Rap1, thus inhibiting their proper localization to membranes. 27 Previous studies suggested inhibition of Ras prenylation as the key molecular mechanism underlying ZOL anticancer activity, 11,28,29 leading to blockade of anti-apoptotic and promitotic downstream signals including the MAPK-and the PI3K/ Akt pathways. 30 Also in osteosarcoma cells, we detected a loss of membrane-associated Ras following ZOL treatment (data not shown).…”
Section: Discussionmentioning
confidence: 99%